Comparer les classes populaires en France et au Portugal: différences structurelles et histoires intellectuelles - Pereira, Virgílio Borges (2017)
This article aims at explaining the difficulties one runs into when comparing works that focus on the lower middle class in France and on the worlds of the Portuguese working class, while emphasizing the intellectually promising nature of such a comparison. The works under scrutiny demonstrate in both cases that the analysis of class positions and class relationships is relevant to the understanding of social inequalities. Yet, both the structure of social spaces and the way of defining and identifying class empirically are not identical. On the one hand, the labor structures, the relative weight of industry and of the rural world, educational policies, the role of the state or the migratory practices differ. On the other hand, different forms of categorization are mobilized in the representation of the social world. This is particularly obvious when it comes to the lower middle classes. While French sociology has gradually expanded its focus from the sociology of the working class to the sociology of the lower middle classes, which brings together under the same analytical scope the worlds of workers and employees, these two social universes remains largely separate in Portuguese society.